2008
DOI: 10.1002/ajhb.20710
|View full text |Cite
|
Sign up to set email alerts
|

Secular changes in body height and weight of Portuguese boys over one century

Abstract: This study examines secular changes in attained height and weight in student boys from a military boarding school (Colégio Militar) in Lisbon, Portugal. Data for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
(25 reference statements)
3
18
1
1
Order By: Relevance
“…Heights of 18-year-old males have increased between 1904 and 2000, and age at menarche has declined (Padez 2007). The trend is consistent with earlier analyses (Padez and Johnston 1999;Padez 2002Padez , 2003Cardoso 2008). By inference, living conditions and associated health benefits have improved in Portugal over the past few decades.…”
Section: Introductionsupporting
confidence: 84%
“…Heights of 18-year-old males have increased between 1904 and 2000, and age at menarche has declined (Padez 2007). The trend is consistent with earlier analyses (Padez and Johnston 1999;Padez 2002Padez , 2003Cardoso 2008). By inference, living conditions and associated health benefits have improved in Portugal over the past few decades.…”
Section: Introductionsupporting
confidence: 84%
“…The increases in height in these peripubertal age groups over the 25 years (5-9 cm for males and 6 cm for females) were statistically significant. The increases were modest when compared to some studies of adolescents in other parts of the world that report height increases in the range of 5-10 cm per decade (Cardoso, 2008;Kurokawa et al, 2008). The magnitude of the estimated pubertal growth spurt in Telefolmin males and females is modest compared to the 8-9 cm per year growth velocity typically seen during puberty in US children (Abbassi, 1998).…”
Section: Stature Of the Mountain Ok At Telefominmentioning
confidence: 87%
“…In Belgium, the rate of increase was also slower than in Poland, and amounted to 1.6 cm per decade for stature over the period from 1920 and 1980 (Hauspie et al, 1996). A study on boys in Portugal from 1899 to 2006 also revealed an average rate of increase of 1.54 cm per decade for stature and 1.54 kg per decade for body weight (Cardoso, 2008).…”
Section: Trends In Body Height and Weight In Polandmentioning
confidence: 93%
“…Intergenerational changes in body weight have been discussed since the 1960s (Cole, 2003), and increases in body weight and body mass index (BMI) in adults, adolescents, and children have been observed in many countries of the world (Cardoso, 2008;Krawczynski et al, 2003;Motton et al 2007). These secular trends include increases in corporal dimensions, especially stature, but also reflect changes in body shape caused by an increase in the accumulation of adipose tissue.…”
Section: Introductionmentioning
confidence: 96%